Spiritual Emotional Freedom Technique Intervention on Anxiety Level of Hypertensive Heart Disease Patients - Rachman, Wa Ode Nova Noviyanti; Rahmadhania, Wa Ode; Indriani, Cece; Yani, Ahmad; Ima, Lukman (Poltekkes Kemenkes Palu, 2023)
Hypertension is one of the leading causes of various heart diseases. In patients with Hypertensive Heart Disease (HHD), anxiety symptoms can continue to increase, which can affect the treatment and healing process and can cause various complications. This study aims to determine the effect of Spiritual Emotional Freedom Technique (SEFT) therapy on anxiety levels in HHD patients in the ICCU room of Kendari City Hospital. This type of research is a pre-experiment with a one-group pretest-posttest design. The population in this study were all HHD patients treated in the ICCU room of Kendari City Hospital. The sampling technique used was purposive sampling, with a total sample size of 22 respondents. This research instrument uses the Anxiety Visual Analog Scale (VAS-A) questionnaire sheet to measure anxiety levels. The analysis method uses a paired-sample t-test. The results showed that the level of anxiety before and after SEFT therapy decreased. This can be seen from the statistical test p-value = 0.000 < α = 0.05, which shows a significant difference. It can be concluded that SEFT therapy influences reducing anxiety levels in HHD patients. It is expected for service institutions and other institutions to provide training for health workers to perform SEFT therapy to help reduce patient anxiety levels.